Monitoring and modelling of water quality characteristics along a reticulation system: a case study of modimolle reticulation network - Mehlo, Mahlomola (My University, 2012)
Potable water quality can deteriorate immensely from point of treatment to point of usage. This change in quality along a bulk distribution main may be attributed to numerous factors, such as the ingress of storm water. Furthermore, water utilities experience challenges in terms of the microbiological organisms that are not attributed to operational practices. For example, drinking water bulk distribution mains may be a shelter for these microorganisms that are sustained by organic and inorganic nutrients present within the pipe itself. These microorganisms may be active in the water being transported by the pipe, and can cause a significant drop in the water quality. In order to deal with the problem of deteriorating water quality, sufficient information within the bulk main is required, so that the consumer can be protected from ingesting contaminated water or water of poor quality. Hence, the overall objective of this study was to investigate and model water quality characteristics within the Modimolle reticulation network. Water samples were collected from various points throughout the entire system for quality analysis. Different sampling points were established along the main pipeline as well as within the Modimolle distribution system. Water quality software, EPANET, was then used to model the water quality deterioration for both the bulk line and the reticulation network of Modimolle extension 11. Residual chlorine was the main parameter which was monitored. This study presents results of a research on water quality variation within a long distribution mains conveying water up to 87 km. Results show that raw residual chlorine is constantly depleted along the pipeline, and is therefore unable to be maintained at the required level of 0.2 mg/l, as stipulated by the Department of Water Affairs. This means that if any harmful contaminants should enter the water, the residual chlorine in the water will not be able to protect the consumers from the contaminants.
M. Tech. (Department of Civil Engineering and Building, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Monitoring; Water quality; Water treatment.; Network modelling.; Modimolle.; Dissertations, Academic -- South Africa.; Water supply -- South Africa.; Water reuse -- South Africa.; Water -- Purification.